Effects of Scorpion Venom Heat-Resistant Protein on Seizure Behavior and Expression of Proenkephalin in Rats with Kainate-Induced Epilepsy - Sun, Y.; Cui, X.; Yin, Sh; Yu, D.; Li, Sh.; Zhang, W.; Zhao, J. (Нейрофизиология, 2013)
Scorpion venom is a traditional antiepileptic medicine in Asia. We examined the effects
of scorpion venom heat-resistant protein (SVHRP) on seizure behavior of rats with
kainate-induced epilepsy and expression of proenkephalin (pENK) in their hippocampus.
Subcutaneous injections of convulsive doses of kainic acid (KA, 10 mg/kg) evoked acute
epileptic seizures; the intensity of such seizures was measured after subsequent injections
of lower (subthreshold in the norm) doses of KA (5 mg/kg). Scorpion venom heat-resistant
protein in a dose of 125 mg/kg was given in a part of the animals through i.p. injections
daily during 10 days; rats of the control groups were injected with normal saline. Behavioral
indices were measured, and the hippocampus was taken for pENK mRNA estimation by RTPCR analysis. The mean behavioral score of seizure sensitivity in the SVHRP-treated group
was smaller significantly (P < 0.05) compared to that in the control group (1.19 vs 2.93).
The pENK mRNA level was dramatically greater in hippocampal neurons of KA-treated rats
with a high seizure sensitivity, while in the SVHRP-treated group the respective index was
significantly lower. Thus, SVHRP inhibits behavior seizures in epilepsy and reverses the
abnormally increased pENK mRNA in hippocampal neurons of such animals Отрута скорпіона є традиційним антиепілептичним терапевтичним засобом в Азії. Ми вивчали вплив термостійкого
протеїну з отрути скорпіона (ТСПОС) на судорожну поведінку щурів з викликаною каїнатом епілепсією та на експресію проенкефаліну (пEНК) у їх гіпокампі. Підшкірні ін’єкції
«конвульсивних» доз каїнової кислоти (КК, 10 мг/кг) призводили до розвитку гострих епілептичних судом; інтенсивність таких судом вимірювали після наступних ін’єкцій КК
(5 мг/кг, підпорогова доза в нормі). Частина тварин отримувала ТСПОС у дозі 125 мкг/кг шляхом внутрішньоочеревинних ін’єкцій щоденно протягом 10 днів; щурам контрольної групи вводили фізіологічний розчин. Вимірювали
поведінкові показники; гіпокамп ізолювали для подальшої
оцінки пEНК мРНК з використанням RT-PCR-аналізу. Усереднені поведінкові показники судомної чутливості в групі
тварин, котрі отримували ТСПОС, були істотно нижче (P < 0.05) таких у контрольній групі (1.19 проти 2.93). У нейронах гіпокампа щурів із високою судомною чутливістю,
котрі отримували КК, рівень пЕНК мРНК був істотно вищим, тоді як у тварин з ін’єкціями ТСПОС відповідний показник був значно нижчим. Отже, ТСПОС гальмує поведінкові судоми при епілепсії та різко зменшує аномально
збільшений рівень пEНК мРНК у нейронах гіпокампа таких тварин.